2015
DOI: 10.1080/08998280.2015.11929303
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antiplatelet Compared to Triple Antithrombotic Therapy in Anterior Wall Acute Myocardial Infarction Complicated by Depressed Left Ventricular Ejection Fraction

Abstract: Current guidelines recommend triple antithrombotic therapy (TT) consisting of warfarin, aspirin, and a P2Y12 inhibitor following an anterior ST elevation myocardial infarction (STEMI) complicated by extensive wall motion abnormalities. This recommendation, however, is based on data collected before percutaneous coronary intervention (PCI) became the standard of care for the treatment of STEMI. We designed a retrospective study of patients who received PCI for anterior STEMI over an 8-year period to compare rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…associated with a reduction in MACEs [43][44][45] and may in fact increase major bleeding. [46][47][48] However, these observational studies are limited by significant biases, including indication bias.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…associated with a reduction in MACEs [43][44][45] and may in fact increase major bleeding. [46][47][48] However, these observational studies are limited by significant biases, including indication bias.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…No published randomized trials specifically address full-dose anticoagulation for the prevention of LV thrombus among patients with MI in the PCI era. Several contemporary observational studies have suggested that the addition of anticoagulation to DAPT to prevent LV thrombus among patients with anterior MI is not associated with a reduction in MACEs 43–45 and may in fact increase major bleeding. 46–48 However, these observational studies are limited by significant biases, including indication bias.…”
Section: Prevention Of LV Thrombus After Acute Mimentioning
confidence: 99%
“…First, only a minority of patients had a repeat TTE by 4 months and the use of contrast media was at the echocardiographer’s discretion. This issue is common to recent retrospective analyses 8 , 21 , 22 . Second, although clinical follow-up at 4 months was available for most patients, the occurrence of specific clinical events was not prospectively assessed or adjudicated.…”
Section: Discussionmentioning
confidence: 95%
“…The reported incidence of LVT formation and subsequent embolization varies based on the timing of the echocardiographic examination and the diagnosis, anticoagulation, and reperfusion strategies utilized in managing the initial presentation. However, it is estimated to range from 0 to as high as 86% [7,8]. A study conducted by Zia et al has reported LVT formation in 15.4% of patients with anterior wall acute myocardial infarction (AWMI).…”
Section: Introductionmentioning
confidence: 99%